The Role of Consumption Values in Shaping Household Shopping Behavior through Food Delivery Apps - Sangadji, Suwandi S.; Gia Mutiarasari, N Azizia; Krisnawati, Wenti (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2024)
This research investigates how consumption values influence changes in consumer behavior, specifically among non-working housewives in Gresik Regency, in their utilization of food delivery applications (FDAs). A qualitative case study methodology was adopted, featuring in-depth interviews with non-working housewives who have used FDAs at least three times. Data collection involved participant observation, interviews, and document analysis, with thematic analysis employed for data interpretation. Findings reveal that both functional and epistemic values significantly influence consumer behavior. Functional value, characterized by convenience, time efficiency, and a diverse range of meal options, serves as a primary motivator for housewives preferring FDAs over traditional cooking. Furthermore, epistemic value is important, as users rely on reviews, ratings, and promotions to inform their decisions. Although some participants expressed concerns about pricing and occasional order cancellations, FDAs have become essential for meal planning among those seeking convenience and variety. This study sheds light on the consumption patterns of non-working housewives and provides practical recommendations for businesses in the food delivery sector to improve consumer satisfaction and loyalty.